Hubungan Mean Arterial Pressure (MAP) Dengan Preeklamsia Pada Ibu Hamil Di Puskesmas Bontobangun Kabupaten Bulukumba - Ely Kurniati; Rusnawati (Jurnal Kesehatan Panrita Husada, 2020)
Preeclampsia complicates 4-7% of pregnancies and remains the leading cause of maternal and fetal morbidity and mortality worldwide. Despite improvements in health care over the last decade, preeclampsia remains the second most common cause of maternal mortality in Indonesia. This study aims to determine whether the mean arterial pressure (MAP) is related to the incidence of preeclampsia in pregnant women at the Bontobangun Puskesmas, Bulukumba district for the period 2018 to 2019. This research uses a descriptive-analytic approach with Historical Cohort Studies, namely by looking at the cohort book of the history of blood pressure measurement results for pregnant women at the Bontobangun Public Health Center, Bulukumba Regency for the period 2018 to 2019. Determining the sample using the sampling method taken by purposive sampling. 31 samples of pregnant women who experienced preeclampsia and 31 controls were pregnant women with normal conditions who had certain criteria (matching) with the sample. The results explained that from the paired T-test results, the value of α> 0.037 so that it is said that there is a relationship between mean artery pressure (MAP) and the incidence of preeclampsia in pregnant women at Bontobangun puskesmas for the period 2018-2019.